Prevalence and determinants of diabetes mellitus in Puducherry, South India - Dharamvir Ranjan Bharati; Ranabir Pal; Sumit Kar; R Rekha; T V Yamuna; Mausumi Basu (Wolters Kluwer Medknow Publications, 2011)
Background : Diabetes mellitus is an emerging global health problem. It is a chronic, noncommunicable, and expensive public health disease. Aims and Objectives : To determine the prevalence and the risk factors of type 2 diabetes mellitus among the adult population of Puducherry, South India. Materials and Methods : This was a population-based cross-sectional study carried out during 1 st May 2007-30 th November 2007 in the rural and urban field practice area of Mahatma Gandhi Medical College and Research Institute, Puducherry. Simple random sampling technique was used for the selection of 1370 adult 20 years of age and above. Main outcome measures were the assessment of the prevalence of prevalence and correlates of diabetes among the adult population. Predesigned and pretested questionnaire was used to elicit the information on family and individual sociodemographic variables. Height, weight, waist, and hip circumference, blood pressure was measured and venous blood was also collected to measure fasting blood glucose, blood cholesterol. Results : Overall, 8.47% study subjects were diagnosed as diabetic. The univariate analysis and multivariate logistic regression analysis showed that the important correlates of diabetes mellitus were age, blood cholesterol, and family history of diabetes. The findings were found to be statistically significant. Conclusions : In our study we observed that adults having increased age, hypercholesterolemia, and family history of diabetes mellitus are more likely to develop diabetes mellitus.